2016
DOI: 10.3892/or.2016.4725
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of autophagic flux by ROS promotes apoptosis during DTT-induced ER/oxidative stress in HeLa cells

Abstract: Abstract. As targets for cancer therapy, endoplasmic reticulum (ER) stress and autophagy are closely linked. However, the signaling pathways responsible for induction of autophagy in response to ER stress and its cellular consequences appear to vary with cell type and stimulus. In the present study, we showed that dithiothreitol (DTT) induced ER stress in HeLa cells in a time-and dose-dependent fashion. With increased ER stress, reactive oxygen species (ROS) production increased and autophagy flux, assessed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 42 publications
(47 reference statements)
0
31
0
Order By: Relevance
“…And impaired autophagic flux has been reported to contribute to apoptosis in various cells, such as retinal neuronal cells, myocardial cell 46 , 47 . Furthermore, ROS was reported to disturb autophagic flux and promote apoptosis during DTT-induced ER/oxidative stress in HeLa cells 48 . In our study, we found that ROS was elevated in NP cells with TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…And impaired autophagic flux has been reported to contribute to apoptosis in various cells, such as retinal neuronal cells, myocardial cell 46 , 47 . Furthermore, ROS was reported to disturb autophagic flux and promote apoptosis during DTT-induced ER/oxidative stress in HeLa cells 48 . In our study, we found that ROS was elevated in NP cells with TNF-α stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of autophagic flux promoted cell apoptosis [ 26 ]. Recent studies suggested that autophagy and apoptosis are connected.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple connections established between the cellular redox state and autophagy [36]. A recent study has reported that increased ROS generation induced autophagic flux inhibition in HeLa cells under stress conditions [37]. CA-5f remarkably elevated ROS levels in A549 cells and HUVECs, which was reversed by the antioxidant N-acetyl cysteine (NAC), but not by diphenyleneiodonium (DPI), a specific inhibitor of NADH/NADPH oxidase (Fig.…”
Section: Ca-5f Suppressed the Expression Of Cytoskeletal And Membranementioning
confidence: 98%